(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Students in today’s classroomshave grown up using an array oftechnology tools and applications. For educators in the information age,technological literacy is critical. The potential of digital storytelling as aninstructional tool for teachers and students has yet to be fullyrealized.Addressing both the cognitive and affective domains, digital storiesare personal narratives supported by images, video, voiceover, soundtrack, andeffects. This article explicates some ofthe pedagogical benefits of digital storytelling in the classroom.Additionally, the paper discusses how digital storytelling can be used toaddress areas of focus identified by two standards-setting agencies that influenceeducational policy.